PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LEVERAGE, UMUR PERUSAHAAN, DAN DEWAN KOMISARIS INDEPENDEN DALAM PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - LINDA SANTIOSO; ERLINE CHANDRA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2012)
The purpose of this study was to determine whether there is influence of profitability, firm size, leverage, firm age, and the proportion of independent board to disclosure of corporate social responsibility. Samples used in this study were 45 manufacturing companies listed on the Stock Exchange in 2008 until 2010 with the disclosure of social responsibility and financial summary data can be obtained through the annual report. Sampling techniques performed by the method of purposive sampling and data processing performed by multiple linear analysis. The study was partially obtained show that profitability, firm size and proportion of independent board effect on CSR disclosure. On the other hand, the partial results showed that the absence of leverage effect and the age of the company towards CSR disclosure.